WHATSAPP USE ON READING COMPREHENSION: EXPLORING THE IMPACT AMONG EFL LEARNERS - Sri Mujayanah; Nirwanto Maruf; Slamet Asari (English Review: Journal of English Education, 2023)
The study aimed to explore the impact of WhatsApp use on reading comprehension among English as a Foreign Language (EFL) learners in Indonesia. Results from the questionnaire showed that a majority of the participants used WhatsApp for reading activities often or very often, with new articles, fiction or literature, and non-fiction books being the most common types of reading materials accessed. The majority of EFL learners spent 1-2 hours on WhatsApp for reading activities, and cited convenience and accessibility as the main reasons for using the platform. The results also showed a significant number of EFL learners believed that using WhatsApp had improved their reading comprehension skills, although some participants did not find it to be an effective tool. The most commonly cited advantage of using WhatsApp for reading activities was convenience and accessibility, followed by engagement with peers and opportunities for discussion and exchange of ideas. Meanwhile, the most commonly cited disadvantage was distraction from other conversation or notifications, limited access to a wide range of reading materials, and lack of interaction with the teacher or tutor. The results also indicated that the majority of EFL learners improved their reading comprehension skills over time when using WhatsApp for reading activities, with a focus on reading texts or materials, participating in group discussions, and completing reading comprehension exercises. The study results provide valuable insights into the impact of WhatsApp use on reading comprehension among EFL learners and could help identify areas for improvement in utilizing the platform for reading activities.